GENDER LANANG SEBAGAI MANIFESTASI BUDAYA AREK DALAM KARAWITAN JAWA TIMURAN - Ahmad Muzaqqi; Warih Handayaningrum; Eko Wahyuni Rahayu (Institut Seni Indonesia Surakarta, 2023)
Gender lanang is a dominant instrument in the karawitan gagrak Jawa Timuran, which illustrates how the dialectics of arek culture society are so egalitarian, outspoken, which distinguishes between Surakarta and Yogyakarta styles, with a psychological, social, and cultural approach, how the gender lanang instrument with a high tone depicts the character of arek society in dialect, which in fact the gender lanang instrument uses high notes.